Before the Ice Disappears: Pursuing Climate Justice for Inuit Women in the Context of Mining in Nunavut - Bellehumeur, Angeline (Scholarship@Western, 2020)
The Arctic’s rapid warming is increasing the potential for mining activity in Nunavut, and, consequently, Inuit women are increasingly at risk of experiencing the adverse and gendered impacts of mining, including gender-based violence. Through a theoretical framework influenced by feminism, Indigenous legal scholarship and legal anthropology, this thesis examines the flaws in the mining industry’s voluntary efforts to acquiring a social licence to operate and in the Nunavut mining regulatory regime, while also considering how the law can provide legal recourse through tort actions and Inuit Impact Benefit Agreements. In every instance, is clear that climate justice for Inuit women in Nunavut mining communities cannot be achieved without applying a gender-based analysis to laws and policies and that Inuit women must be afforded the opportunity to govern their own lives.